FRACTIONAL MATHEMATICAL MODELLING OF THE CORROSION RATE OF ALUMINUM 5083 IN A MARITIME ENVIRONMENT - Muhammad Rifki Nisardi; Nur Rahmi; Muhammad Arkam Arifuddin; Hartina Husain; Kusnaeni Kusnaeni (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
Aluminum 5083 is one of the materials used for the construction of ship hulls due to its classification as a material with good corrosion resistance. Despite its high corrosion resistance, Aluminum 5083 remains susceptible to galvanic corrosion and pitting corrosion caused by marine environmental conditions. This study develops a mathematical model by adding chloride and passivation effects using fractional differential equations to describe the corrosion rate of Aluminum 5083. The model construction using a Fractional Differential Equation System (FDES) aims to capture memory effects to represent the complex corrosion dynamics accurately. Stability analysis of the fractional model shows that the system is locally asymptotically stable, with all eigenvalues satisfying the condition . Furthermore, a numerical solution approach using the PECE-PI method is employed to solve the model, demonstrating agreement between the simulation results and real-world corrosion phenomena. Involvement of different fractional orders α reveals an effect on the rates of increase and decrease in concentration for each variable. The smaller the value of fractional order α, the slower the concentration change process occurs.